The terminal pleistocene of Klipfonteinrand rock shelter in the Cederberg - Bluff, Kyla Catherine Pelton (Department of Archaeology, 2018)
This thesis focuses on Klipfonteinrand Rock Shelter in the eastern Cederberg, during the Late Pleistocene period (22.3 - 13.4 cal kyr BP), and specifically the materials analysed after the completion of excavations at the site. The study aims, firstly, to unpack changes in the composition of the archaeological assemblage of Klipfonteinrand during Marine Isotope Stage 2 (MIS 2), by analysing variation in the abundance and composition of lithics, ostrich eggshell, marine shell, charcoal, ochre, bone and roof spall from the site; and, secondly, to situate these changes in the context of changes in palaeoenvironments and patterns in the use of nearby and more distant archaeological sites. Results display a hornfels-dominant lithic assemblage, with a distinctive silcrete-rich Robberg-like industry during the period 22.3 - 16.3 cal kyr BP, categorised by micro-bladelets and bipolar cores. Ostrich eggshell fragments undergo variation in thickness in relation to variation in environmental and climatic changes, and also contain a handful of decorated fragments that mirror a sample from Boomplaas during a similar time period. Donax serra dominates the marine shell assemblage, which peaks in number between 16.6 and 15.9 cal kyr BP, at the time of rapid sea level rise across the subcontinent. Links are drawn between Klipfonteinrand and sites further afield such as Elands Bay Cave, based on the movement of hornfels from the interior to the coast and marine shell from the coast to the interior at the time of sea level rise. Roof spall is smallest and most abundant during colder periods, and charcoal and bone are most abundant then too. Red ochre is the most frequently occurring colour, with ochre having been ground most frequently in the younger levels between 14.4 - 13.4 cal kyr BP. These results are drawn together and Klipfonteinrand Rock Shelter is contextualised in a larger framework of MIS 2 archaeology and palaeoenvironments, on a local, regional and inter-regional scale. The various materials recovered from the excavation show specific diachronic patterns and suggestions are made about lithic technologies, craft and design, and complex landscape use of Late Pleistocene hunter-gatherers. The overarching purpose of this is to attempt to gain a better understanding of human behaviour during the environmentally unstable time period presented.